ANALISIS TATA LETAK FASILITAS PRODUKSI TAS “RUMAH WARNA” : Studi Kasus Pada Pabrik Tas Rumah Warna Di Desa Semawung Kecamatan Kutoarjo (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this study is to analyze the layout of production facili ties on the row of Rumah Warna Bags so as to form an ideal process flow, effective and efficient. Limitations of the problem in this study only on the layout of production facilities is limited to the bag production room in the period of study year 2016 - 2017. Data analysis technique used in this study is using the operation process map, process sequence sheet, activity relationship map, and the diagram of the allocation of territory . Technique used in presenting data of research result that is using wor kflow diagram and flow of production process and diagram about layout and method. Result of research using operation process map there are 11 bag making operation process with total time taken for whole process is 20,75 minutes and mean time each process 1 ,88 minutes. Based on the process sequence of the whole process from start to finish process using 1 pencil pattern, 1 pattern cutting machine, 4 tools of giving glue, 5 actual sewing machine, 1 actual obras machine, 2 pieces of tweezers and 1 scissors for quality control and isolatape for packing process. Result of analysis of activity relation map, production room has 3 level of importance, 6 description of reason, packing space 2 level of interest, 3 description of reason, process space pattern 2 level o f interest, 5 description of reason, warehouse area 2 level of interest, 2 description of reason, 2 levels of importance, 2 description of reasons. From the results of the allocation diagram of the pattern space area, and the raw material warehouse and pac king room previously located outside the production area after the analysis based on the level of interest is now in the production area